Phylogenomic Analysis of Two Species of Parasenecio and Comparative Analysis within Tribe Senecioneae (Asteraceae) - Xiaofeng Liu; Junjia Luo; Mingke Zhang; Qiang Wang; Jie Liu; Die Wu; Zhixi Fu (Diversity, 2023)
The genus of Parasenecio (Senecioneae) comprises about 70 species of high medicinal value. In this study, the plastomes of Parasenecio palmatisectus and P. latipes were newly sequenced using high-throughput sequencing technology and compared with those of eight other species in Senecioneae. The complete chloroplast (cp) genomes were 151,185 bp in P. latipes with 37.5% GC and 151,263 bp in P. palmatisectus with 37.5% GC. We predicted 133 genes, including 37 tRNA genes, 86 protein-coding genes, 8 rRNA genes, and 2 pseudogenes (ycf1 and rps19). A comparative genomic analysis showed that the complete cp genome sequences of Parasenecio species and their related species were relatively conserved. A total of 49 to 61 simple sequence repeats (SSRs) and 34 to 46 interspersed repeat sequences were identified in the 10 Senecioneae species of plastomes. Within the tribe Senecioneae, single-copy regions were more variable than inverted repeats regions, and the intergenic regions were more variable than the coding regions. Two genic regions (ycf1 and ccsA) and four intergenic regions (trnC-GCA-petN, ycf1-trnN-GUU, psaI-ycf4, and rpl32-trnL-UAG) were identified as highly valuable plastid markers. A phylogenetic analysis under maximum likelihood revealed that the two Parasenecio species are sister to the genera of Ligularia and Sinosenecio in the tribe Senecioneae. This study also contributes to the super-barcode, phylogenetic, and evolutionary studies of Parasenecio plants.